THE ROLE OF THE WORLD HEALTH ORGANIZATION (WHO) IN MANAGING OF EBOLA OUTBREAK IN THE DEMOCRATIC REPUBLIC OF THE CONGO (2018-2019) - Chairani, Rury; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
An epidemic of a disease is an issue that can worry the international community that can affect national and global activities. One of the outbreaks that have caught the world's attention is the Ebola epidemic that occurred in the Democratic Republic of Congo in 2018-2019. The Ebola epidemic that occurred in the Democratic Republic of Congo in 2018-2019 was the largest outbreak in the history of the Democratic Republic of Congo and the second largest in the world after the Ebola epidemic that hit Liberia, Sierra Leone and Guinea in 2016. The purpose of this study is to determine the role WHO as the World Health Organization in controlling the Ebola outbreak caused by the Ebola virus.In this study, the author uses a pluralism perspective which assumes that the state is not always the main actor and the sole actor and group behavior as the level of analysis. The theory used in this research is the theory of international organizations which emphasizes that international organizations are formal, sustainable structures that are formed by mutual agreement and play an important role in international relations. This research method uses descriptive research methods with a qualitative approach.The research finds that WHO is working with local, regional governments and partners to managing the Ebola outbreak. WHO also acts as an Instrument, Arena and Actor as a form of commitment to controlling the outbreak. Various steps were taken through various programs such as, socialization, investigation, vaccination, coordination, operational support, logistics and funds aimed at minimizing transmission of the Ebola virus. WHO and its partners continue to strive to deal with this outbreak to achieve the highest possible level of health in line with the WHO Goals.Keywords: Democratic Republic of the Congo, WHO, Ebola Outbreak